2019
DOI: 10.18502/kss.v3i22.5119
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Practice Disclosure of Malaysian Public Listed Companies

Abstract: The Malaysian corporate environment has been shocked by corporate scandals and poor performance among government-related companies, such as 1Malaysia Development Berhad (1MDB), Lembaga Tabung Haji (LTH), Felda Global Ventures (FGV) and Khazanah Nasional Berhad (KHAZANAH). Despite having strong corporate governance and being strengthened through Malaysia Code of Corporate Governance (MCCG), unethical practices and a lack of transparency remain a problem among Malaysian companies. The purpose of this paper is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The scenario above reflects that complying with corporate ethical conduct for disclosures among Malaysian companies is still a problem. This finding is consistent with the National Anti-Corruption Plan 2019-2023 or NACP on the lack of control and transparency in corporate governance (Abidin et al, 2019). This gives rise to why there is still low awareness of the importance of ethical practices disclosures among companies.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…The scenario above reflects that complying with corporate ethical conduct for disclosures among Malaysian companies is still a problem. This finding is consistent with the National Anti-Corruption Plan 2019-2023 or NACP on the lack of control and transparency in corporate governance (Abidin et al, 2019). This gives rise to why there is still low awareness of the importance of ethical practices disclosures among companies.…”
Section: Introductionsupporting
confidence: 85%
“…Under ethical commitment, past studies have identified six sub-categories: corporate ethical values, action to promote ethics, whistleblowing policy, code of ethics disclosure, corporate commitment towards sustainability, and the availability of the Ethics Committee (Rahman et al, 2016;Abidin et al, 2017Abidin et al, , 2020Abidin et al, 2019;Salin et al, 2019;Hashim et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations